2018
DOI: 10.1002/adsc.201701546
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Nazarov Cyclizations Catalyzed by Chiral‐at‐Metal Complexes

Abstract: The application of Lewis acidic chiral-atmetal complexes of iridium(III) and rhodium(III) as catalysts for the asymmetric polarized Nazarov cyclization of dihydropyran-and indole-functionalized a-unsaturated b-ketoesters is reported (overall 24 examples). For both substrate classes, catalyst loadings of 2 mol% were found to be sufficient for achieving high yields and high stereoselectivities. The cyclized dihydropyran products were isolated in 85-98% yield, with 89%-> 99% ee, and trans/cis ratios of 15:1-50:1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 57 publications
0
21
0
1
Order By: Relevance
“…Recent interest on cyclopentenyl cations 1 stems from their intermediacy in important organic (Nazarov cyclization –formation of cyclopentenones) and industrial processes (methanol‐to‐hydrocarbon conversion) . Historically however, it was the presence of a C=C double bond in close proximity to a cationic sp 2 carbon center, and hence the possibility of gaining “extra stabilization” by allylic or homoaromatic delocalization, that put this system into the focus of carbocation chemistry .…”
Section: Introductionmentioning
confidence: 99%
“…Recent interest on cyclopentenyl cations 1 stems from their intermediacy in important organic (Nazarov cyclization –formation of cyclopentenones) and industrial processes (methanol‐to‐hydrocarbon conversion) . Historically however, it was the presence of a C=C double bond in close proximity to a cationic sp 2 carbon center, and hence the possibility of gaining “extra stabilization” by allylic or homoaromatic delocalization, that put this system into the focus of carbocation chemistry .…”
Section: Introductionmentioning
confidence: 99%
“…As a second model reaction, we chose an asymmetric Nazarov cyclization [ 49 , 50 ]. We recently demonstrated that Λ- IrS (2.0 mol%) is an excellent chiral Lewis acid for the conversion of ketoester 6 to the cyclopentenone (1 R ,2 S )- 7 ( Table 2 ) [ 51 ]. Using the same established reaction conditions, after a reaction time of 7 hours in hexafluoroisopropanol [ 52 ] at 50 °C, followed by base-induced isomerization to the thermodynamic trans diastereomer, (1 R ,2 S )- 7 was obtained in 75% yield with 15:1 dr and 93% ee.…”
Section: Resultsmentioning
confidence: 99%
“…[86] Enantio selective reactions such as enantio selective Nazarov cyclisation is also performed by iridiumbased chiral catalyst. [87] Ir-based catalysts are particularly important in organic synthesis and oxidation reactions such as oxidation of primary, secondary alcohols, phenols, amines, phosphines, alkane, alkenes and aromatic compounds. [88] Importance of iridium as catalyst in organic synthesis is proven by various reactions viz.…”
Section: Iridium-based Catalystsmentioning
confidence: 99%